Level of Social Interest in Teachers Improving Their Professional Qualification - Nedelina Zdravkova (Педагогически форум)
The article is devoted to the key concept of the creator of individual psychology A. Adler about social interest as a potential and predictor of socially useful personality activity. In the specific study, the form of manifestation of social interest is referred to as “lifelong learning”, ensuring and maintaining high qualification of the teachers. Establishing the level of social interest of qualifying teachers mainly within the limits of high, advanced and medium levels confirms the thesis of the increased social responsibility of educators in realizing the tasks of education and upbringing.